Pencil beam scanning proton therapy of Hodgkin's lymphoma in deep inspiration breath-hold: A case series report. (March 2020) - Andersson, Karin M.; Edvardsson, Anneli; Hall, Annika; Enmark, Marika; Kristensen, Ingrid
Highlights: A combination of proton therapy and deep inspiration breath-hold can reduce normal tissue dose. The first patients treated showed clinically acceptable inter breath-hold variations. The treatment strategy is robust and works well at a proton center. Abstract: Background: Most patients with Hodgkin's lymphoma are young and have a favourable prognosis, therefore it is of high importance to decrease the radiation doses to normal tissues received during radiotherapy. A combination of proton therapy and deep inspiration breath-hold technique (DIBH) can improve the sparing effect and thereby reduce the risk of late effects. Case presentation: The two first patient cases treated with proton therapy in DIBH at the Skandion Clinic, Uppsala, Sweden, are presented here. Proton treatment plans were compared to photon plans based on doses to target and organs at risk. Several CT scans were acquired during the treatment course and inter breath-hold variations were evaluated based on anatomical distances and dosimetric comparisons. Conclusions: The results from our first patients treated with proton therapy in DIBH imply that the treatment strategy is robust and has the potential to reduce dose to normal tissue.